2011
DOI: 10.1007/s00018-011-0816-1
|View full text |Cite
|
Sign up to set email alerts
|

Antithetic roles of proteoglycans in cancer

Abstract: Proteoglycans (PGs), a family of complex post-translationally sculptured macromolecules, are fundamental regulators of most normal and aberrant cellular functions. The unparalleled structural-functional diversity of PGs endows them with the ability to serve as critical mediators of the tumor cells' interaction with the host microenvironment, while directly contributing to the organization and dynamic remodeling of this milieu. Despite their indisputable importance during embryonic development and in the adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 247 publications
(198 reference statements)
0
38
0
Order By: Relevance
“…Syndecan-1 (SDC1) has dual roles in different cancer types by being either an inhibitor or promoter of tumor progression [14]. It is involved in cell proliferation, adhesion, migration, and angiogenesis, but its expression diverges in various tumor types [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syndecan-1 (SDC1) has dual roles in different cancer types by being either an inhibitor or promoter of tumor progression [14]. It is involved in cell proliferation, adhesion, migration, and angiogenesis, but its expression diverges in various tumor types [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in cell proliferation, adhesion, migration, and angiogenesis, but its expression diverges in various tumor types [14][15][16]. Generally, SDC1 expression is higher in epithelial malignancies than in mesenchymal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is a body of evidence suggesting that statins, which are inhibitors of the HMG-CoA reductase pathway (blocking isoprenoid synthesis), may benefit cancer therapeutics (56). Intermediate filaments are widely used as markers of cancer differentiation and prognosis (57, 58), while proteoglycans are known mediators of tumor cells interaction with their microenvironment and regulators of angiogenesis (59, 60). Oxidoreductase activity plays a role in cancer too, since a recent meta-analysis of 21 studies has shown that polymorphisms in the NAD(P)H quinine oxidoreductase 1 ( NQO1 ) gene are significantly associated with digestive tract cancer risk among Europeans and Asians (61).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that reduction of cancer cell adhesion and spreading by using monoclonal antibody against the NG2/CSPG4 core protein [49] or enhancement of cancer cell metastasis by using the NG2/CSPG4-null cancer cells [33] suggest that NG2/CSPG4 may be a key factor in integrin-controlled cancer cell adhesion [9,54]. Other signaling pathways such as Wnt [55,56], Prolantin-jak-2-Stat-5 [56], GTPaseRac-Rho [10], ERK1/2 [9] and PI3K/AKT [54] can also be originated by NG2/CSPG4 but are beyond our discuss scope in this review.…”
Section: Activated Ng2/cspg4 Proteoglycan In Cancer Cell Adhesion (Camentioning
confidence: 99%
“…NG2/CSPG4 consists of two chondroitin sulfate proteoglycan components (N-linked 280 kDa, 450 kDa) which express on cell membrane [8]. Since both 280 kDa and 450 kDa comprise of the same core protein but appear to be independently expressed, a challenging would be to ascertain how effectively to what extent to target NG2/CSPG4 in cancer cell matrix action that associates to carcinogenesis [9]. This challenge may be more precise for targeting therapeutics to eventually eliminate progressive malignant cancers and for potential targeting opportunities to develop drugs aimed at theIn the late 1980s, investigators found that NG2/CSPG4 "calms" in progenitor cells but "acts" once the cells make an initial commitment to a particular cellular lineage [21], suggesting that NG2/CSPG4 is not so much a marker for a specific cell type, but is more of a marker for an "activated" (as opposed to quiescent or calm) status of cells.…”
Section: Introductionmentioning
confidence: 99%